Atap Pagoda pada Masjid Langgam Tiongkok - Fitriana, Tiara Rijayanti; Isfiaty, Tiara (Universitas Komputer Indonesia, 2024)
Pagoda roofs as a characteristic of Chinese-style mosques have a multilevel design and can affect the interior aspects. The impact of the pagoda roof on the interior is still quite limited. This research aims to examine the shape of the pagoda roof at Cheng Ho Mosque Surabaya on the function of interior natural lighting, and find the meaning of the roof shape. The method used is architectural morphology analysis based on Nicola Marzot's theory, direct observation data collection and documentation. The results showed that the Cheng Ho Mosque pagoda roof functions as an efficient natural lighting element, has an octagon pattern with stained glass openings, and is a symbol of acculturation of Islamic-Chinese culture and spirituality. This research is expected to contribute theoretically, enriching the understanding of traditional architectural functions that are not only symbolic, but also functional and ecological in the context of cultural acculturation and space efficiency. Keywords: Roof; Mosque; Pagoda; Lighting; Chinesse